Islam Wasathiyah dalam Bingkai Digital Guna Membangun Narasi Moderasi Beragama - Rizki, Putri Zakiyah Ar; ., Muhdi (Jurnal Pendidikan, Sains Dan Teknologi, 2025)
This study examines the role and implementation strategies of Wasathiyah Islam within a digital framework to build a narrative of religious moderation in Indonesia. The development of digital media has transformed patterns of da'wah and religious authority, while simultaneously giving rise to challenges in the form of polarization, hoaxes, hate speech, and immoderate religious content. In this context, Wasathiyah Islam has become an important paradigm emphasizing the values ​​of moderation, balance, tolerance, and justice in religious life. This study uses a descriptive qualitative approach with content analysis techniques on digital da'wah content produced by mainstream Islamic organizations, such as the Indonesian Ulema Council (MUI), Nahdlatul Ulama (NU), and Muhammadiyah, through Instagram, Facebook, TikTok, and YouTube. The results show that digital media plays a strategic role in disseminating the values ​​of Wasathiyah Islam through multi-platform da'wah, digital religious literacy, and the production of counter-narratives against extremist ideologies. The implementation of digital Wasathiyah Islam is carried out through strengthening the role of Muslim preachers and influencers, the formation of a cyber da'wah team, and collaboration between religious and state institutions, particularly the Ministry of Religious Affairs and the Ministry of Communication and Information Technology. This study concludes that strengthening Wasathiyah Islam in the digital space is a strategic step in building inclusive and sustainable religious moderation in Indonesia.